The factors influenced by stakeholder identification in E-learning systems: A survey - H. Elneel, Duha Awad; Kahtan, Hasan; Abdul Sahli, Fakharudin; Abdulhak, Mansoor; Al-Ahmad, Ahmad Salah; A lzoubi, Yehia Ibrahim (Science Direct, 2023)
Identifying the appropriate stakeholder is an integral part of the requirements engineering process and the primary factor influencing system success. The E-learning system is a significant platform with a variety of stakeholders that must be identified. After the launch of the E-learning system, issues such as identifying stakeholders arise and threaten the system's continuity. Moreover, the use of non-scientific and incompatible methods for identifying stakeholders, as well as the limitations of some of these methods, are among other issues that are highlighted in this research. This study investigates the issue of Stakeholder Identification (SI) in the E-learning system and identifies the most influential factors influencing this significant issue. By conducting a comprehensive literature review and employing qualitative data collection and analysis, these factors are addressed. There were 35 survey questionnaires were distributed to experts, analysts, and developers in the field of the E-learning system in Malaysia in 2022 to collect the data. The results reported in this paper demonstrated that there are difficulties in defining the actual stakeholders, as well as a lack of knowledge in employing the appropriate techniques to identify them, which were then analysed and compared to generate the list of factors. The factors identified in this paper help industries understand how critical it is to identify the actual stakeholders of an E-learning system at an early stage. Therefore, industries should be able to develop stable and reliable E-learning systems. This research provides several contributions, including crucial theoretical and practical insights into how E-learning systems are used and adopted. Contributes to the current literature by outlining the key obstacles caused by SI concerns. Identify the most significant components of SI issues, i.e., information quality, time and cost, system utility, and technology. Finally, this paper provides important recommendations for academics, developers, and regulators, allowing them to better understand the critical factors of effective E-learning system implementation.